Texts, Contexts, and Visuals: Multimodal Meaning-Making in English for Nusantara Comic Strips - Sarah Najla Nafila; Emi Emilia (Jurnal Manajemen Pendidikan dan Ilmu Sosial, 2026)
This study investigates how meaning is constructed through verbal and visual modes in comic strips from the English for Nusantara (EfN) textbook across different grade levels. The study aims to examine how genre, register, and visual composition are integrated to support pedagogical purposes in EFL instructional materials developed in accordance with curricular guidelines. Using a qualitative multimodal discourse analysis, selected comic strips were analyzed using a coding sheet developed as the primary research instrument. The coding sheet enabled a systematic and theory-informed analysis by integrating two analytical layers: linguistic analysis based on Systemic Functional Linguistics, focusing on genre structures and register variables; and visual analysis following Kress and van Leeuwen’s compositional metafunction. The findings reveal that the comic strips consistently realize pedagogical genres such as recount and report texts, with register configurations adapted to learners’ developmental levels. Visual compositional resources systematically reinforce verbal meanings by organizing information and directing readers’ attention. This study concludes that the coherent integration of genre-based linguistic choices and visual compositional resources enhances pedagogical coherence in purpose to supports learner comprehension. The findings provide insights for curriculum and materials development by illustrating how multimodal genre and register choices can be systematically aligned with curricular goals and learners’ developmental stages.